The performance of institutional of dairy cattle farmers and their effects on financial, technological, and physical resources - Soetriono Soetriono; Amam Amam (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
The Performance of Institutional give influences to the development of livestock business, and influenced by farmers' access to various resources. The purpose of this study is to examine the institutional performance of dairy farmers and analyze their effects on resources. The study was conducted in May to September 2019 in Pujon Subdistrict, Malang Regency, East Java Province. Respondents are all breeders of Tirtasari Kresna Gemilang KUB (Joint Business Group) of 174 people. The method of collecting data uses FGD (Focus Group Discussion), observation, and survey. The survey was conducted by interview and questionnaire. The variables of research consisted of institutional performance (X), financial resources (Y1), technological resources (Y2), and physical resources (Y3). Data were analyzed using the PLS (Partial Least Square) method. The results showed that institutional performance affected financial, technological, and physical resources, respectively 0.414, 0.367, and 0.289. The conclusion of the research is the institutional performance of dairy farmers with a positive and significant effect on financial resources, technological resources, and physical resources.